The feasibility of a Swiss complex interprofessional intervention to improve the management of procedural pain in neonates in the Finnish context: A qualitative study - Mäki-Asiala, Mariaana; Balice-Bourgois, Colette; Axelin, Anna; Pölkki, Tarja (Wiley, 2025)
Aim: To evaluate the feasibility of the Swiss complex interprofessional intervention, NEODOL© (NEOnato DOLore), for improving the management of procedural pain in neonates in the Finnish context.
Background: Interprofessional collaboration is important for all professionals involved in the care of neonates and for neonates' parents, to understand the appropriate use of non-pharmacological and/or pharmacological methods for each pain situation and how to assess pain in real-life situations. Appropriate methods of pain relief for neonates should be preferred as they protect the development of the neonate's brain.
Design: A descriptive qualitative design.
Method: Data were collected through semi-structured focus group discussions following the Medical Research Council's framework for evaluation of complex interventions, in this case NEODOL© which aims to improve the procedural pain management of neonates. A purposive sample (n = 13) included eleven professionals representing various professions within Finnish Neonatal Intensive Care Units and two parents of infants who have received care in a Neonatal Intensive Care Unit. Data were analysed using inductive content analysis, and the results were reported in accordance with the COREQ guidelines.
Results: Professionals' and parents' evaluations suggest that NEODOL© is feasible, because it is consistent and addresses a current need. They assessed its overall content to be relevant and accessible, and its components to be internally coherent. However, they emphasise the need for further evaluation and refinement of the intervention to achieve the desired outcomes and cost-effectiveness.
Conclusions: While NEODOL© is considered feasible, it requires further evaluation and refinement in the local context of each hospital before implementation.